(untitled) - Kaplan, Richard L. (Cambridge, U.K.,New York, 2002)
Politics and the American Press takes a fresh look at the origins of modern journalism's ideals and political practices. In particular, Richard Kaplan addresses the professional ethic of political independence and objectivity widely adopted by the US press. He shows how this philosophy emerged from a strikingly different ethic of avid formal partisanship in the early twentieth century. The book also provides fresh insights into the economics of journalism and uses business papers and personal letters of publishers to explore the influence of competition, advertising, and an explosion in readership on the market strategies of the press. Kaplan documents the changes in political content of the press by a systematic content analysis of newspaper news and editorials over a span of 55 years. The book concludes by exploring the question of what should be the appropriate political role and professional ethics of journalists in a modern democracy.
Keywords: Press and politics,Journalism,Chính trị và báo chí,Báo chí; History,Objectivity,History,Lịch sử,Tính khách quan,Lịch sử; 19th century,20th century,19th century,20th century,Thế kỷ 19,Thế kỷ 20,Thế kỷ 19,Thế kỷ 20; United States,United States,Hoa Kỳ,Hoa Kỳ